THE ROLE OF TRADITIONAL ART IN DEVELOPING STUDENTS’ CREATIVITY IN VISUAL ARTS EDUCATION - Nasulloyeva Sarvinoz Komiljon qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article examines the role of traditional art in fostering creativity among students in visual arts education. It highlights the significance of integrating national and cultural art forms into lessons to develop aesthetic literacy, critical thinking, and creative skills. The article discusses practical, interactive, and project-based teaching methods that help students explore and apply traditional artistic elements in contemporary visual art projects.